Nella BRAND IMAGE, CO BRANDING, CUSTOMER SASTIFACTION INFLUENCES TOWARD PURCHASE INTENTION OF HAJJ BAILOUT MULTIPURPOSE BY PERCEIVED VALUE AND BRAND PREFERENCE VARIABLES AS INTERVENING VARIABLES IN PEOPLE CREDIT BANK JOMBANG - Sutikno, Nella Bintari Anjarwati (Archives of Business Research, 2019)
Brand Image, Co-Branding, Customer Sastifaction to the Intention of Purchasing Multipurpose Hajj Loan with perceived Value Variables and Brand Preference as Intervening Variables at Bank Jombang BPR. The research method used is a quantitative method with 100 Multipurpose Credit Hajj Customers in BPR Bank Jombang as Respondents. The results of this study affect the Imaget Brand to Perceived proved to have a significant effect in this study. The effect of Co-Branding on Perceived Value proved to have a significant effect on research.This effect of Customer Sastifaction on Perceived Value proved to be significant in this study. The Effect of Brand Image on Brands proved to have a significant effect in this study. The Effect of Co-Branding on Brand Preference proved to be a significant effect in this study.The influence of Brand Image on Purchase Intentions proved to have a significant effect in this study. Effects of Co-Branding on Purchase Intentions proved to have a significant effect on this study. Effect of Slow Sastifaction ggan against Purchase Intentions proved to have a significant effect in this study. The Effect of Value Perceptions on Purchase Intentions proved to have a significant effect in this study. Effects of Brand Preference on Purchase Intentions proved to have a significant effect on this study